PENGARUH FAKTOR PENGETAHUAN DAN PETUGAS KESEHATAN TERHADAP KON SU MSI OB AT KAK I GAJ AH (FI L ARI ASI S) DI KELURAHAN BLIGO KECAMATAN BUARAN KABUPATEN PEKALONGAN - Imam Purnomo; Supriyo .; Sri Hidayati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Filariasis  or  elephantiasis  disease  in  Indonesia  is  widespread  throughout  the  province. This disease does not cause death , but it can result in lifelong disability , social stigma , as well as psychosocial barriers resulting in lower work productivity of patients , families and communities who cause huge economic losses . Pekalongan is one of the endemic areas of filariasis cases the number is increasing year by year with the number of microfilariae ( mf ) rate of 1 % or more . Subdistrict Buaran is one of filariasis endemic areas with the highest rate Mf of 3.9 % . Filariasis mass  drug  administration strategy  is  to  break  the  chain  of  transmission  of  filariasis  by  mass prevention  approach  to  all  residents  of  filariasis -endemic  areas  .  And  the  Village  Bligo  ranks lowest in drug delivery elephantiasis among Rural / Urban Village in the District Buaran . Based on such information , the author is very interesting to do research on the factors associated with the consumption of drinking drug elephantiasis ( filariasis ) in the Village Bligo Pekalongan .This  research  is an  explanation (explanatory  research) through hypothesis testing with survey method using questionnaires and interviews with a cross-sectional approach. Based on the survey  results  revealed  there  are  significant  effect  knowledge  of  drug  consumption  elephantiasis with p-value of 0.001 , and there are significant effect health  workers against elephantiasis drug consumption in Sub Bligo Pekalongan with p -value of 0.011.Suggestions in this research is to TPE officers are there in the Bligo Village expected to increase  the dissemination of elephantiasis drug that increases Bligo Village community achievement elephantiasis drug consumption by always giving an understanding of the benefits of the drug when distributing drugs elephantiasis elephantiasis.Keywords: filariasis, mass elephantiasis drug consumptionBibliography: 16 Books (years 1994-2010)